MUSICAL BROCHURE CREATED IN THE XI-XIII CENTURIES - Fozilov Qaxramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will talk about the musical brochure created in the XI-XIII centuries, dedicated to Bukhara.